Iatrogenic aspiration of custom-made keel: A case report - Sharouny, H.; Omar, R. (Kowsar Publishing, 2014)
Introduction: Laryngeal stenosis has various causes and treatment options. Endoscopic resection of the stenotic part with CO2 laser is one of the treatment options of laryngotracheal stenosis. Keels are useful for preventing adhesion formation, restenosis and web formation, which may happen during the later stage. They can be put in place either via the endoscopic approach or through a micro thyroidotomy and are held in place with a heavy suture through cricothyroid and thyrohyoid membranes. They are left in place for two to four weeks, and then removed through the endoscopic approach under general anesthetics. Case Presentation: We report on a case of anterior glottis stenosis with keel aspiration for two weeks, after endoscopic CO2 laser resection of the stenotic section and keel placement. The patient was admitted to our center, where bronchoscopy was performed and the keel was removed. A new custom-made silastic keel was properly placed in raw areas and fixed to the skin with suture through the cricothyroid and thyrohyoid membranes. The keel was removed three weeks later. Conclusions: Endoscopic keel placement should be done with heavy suture through cricothyroid and thyrohyoid membranes. Surgeons should suture the keel to the anterior laryngeal wall with specially designed Lichtenberger's needle-carriers to prevent complications such as keel aspiration, adhesion formation and imposing a second trip under general anesthetics, which put the patient at increased risk. The false vocal cord microflaps, as biological keels and a relatively new method may replace silastic keel placement in the future.